Tectonic Influence on the Geomorphology of Submarine Canyons: Implications for Deep-Water Sedimentary Systems - Bührig, Laura H.; Colombera, Luca; Patacci, Marco; Mountney, Nigel P.; McCaffrey, William D. (Frontiers in Earth Science, 2022)
A database-informed metastudy of 294 globally distributed submarine canyons has been conducted with the aim of elucidating the role of tectonic setting on submarine-canyon geomorphology. To achieve this, data from seafloor and subsurface studies derived from 136 peer-reviewed publications and from open-source worldwide bathymetry datasets have been statistically analyzed. In particular, relationships between margin type (active vs. passive) or plate-boundary type (convergent vs. transform vs. complex) have been assessed for key morphometric parameters of submarine canyons, including: streamwise length, maximum and average width and depth, canyon sinuosity, average canyon thalweg gradient, and maximum canyon sidewall steepness. In addition, possible scaling relationships between canyon morphometric parameters and characteristics of the associated terrestrial catchment, continental shelf and slope, and of the broader physiographic setting for canyons along both active and passive margins have been evaluated. The following principal findings arise: (1) overall canyon geomorphology is not markedly different across tectonic settings; (2) slope failure might be more important in passive-margin canyons compared to active ones, possibly due to seismic strengthening in the latter; (3) some aspects of canyon geomorphology scale with attributes of the source-to-sink system and environmental setting, but the strength and sign in scaling might differ between active and passive margins, suggesting that the extent to which canyon geomorphology can be predicted depends on the tectonic setting. Insights from our analysis augment and improve conceptual, experimental and numerical models of slope systems at the scale of individual canyons and source-to-sink systems, and increase our understanding of the complex role played by tectonic setting in shaping deep-water systems.